The influence of the ecuadorian education system on the development of critical thinking in Unified General Baccalaureate - Chamba-Zarango, Alexandra Patricia (2025)
Students' limited ability to analyze texts or synthesize information demonstrates a significant weakness in their ability to critically assess reality. This raises questions such as: What is the current state of Ecuadorian education? How does the educational system influence the development of complex skills and critical thinking? The objective of this work is to investigate the impact of the Ecuadorian educational system on the teaching-learning process, in order to propose activities that promote the development of critical thinking at the high school level. The research was based on analytical-synthetic and hermeneutic methods. The analytical method allowed for relating the foundations of the educational legal framework to classroom teaching processes, while the hermeneutic method facilitated the interpretation of pedagogical work through the interview technique, a technique that proved key to exploring teachers' perceptions and practices and identifying challenges and opportunities in the development of critical thinking. The results highlight the urgency of strengthening students' metacognitive skills, implementing teaching strategies that provide lasting tools for identifying truth criteria in discourse, and developing skills for formulating meaningful questions. It is concluded that Ecuadorian education faces difficulties stemming from reforms influenced by government interests, inadequate curriculum management, and insufficient teacher preparation. Overcoming these barriers requires a renewed approach that prioritizes critical education, fosters intellectual autonomy, and revitalizes the commitment of the educational system.